HUBUNGAN LINGKUNGAN KERJA NON FISIK, KEMAMPUAN KERJA DENGAN KINERJA PEGAWAI KELURAHAN KILONGAN KECAMATAN LUWUK UTARA KABUPATEN BANGGAI - Jurtan Latuba (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The purpose of this study is to determine whether the non-physical work environment, the ability to work related to the district office employee performance kilongan District of North Luwuk Banggai .. The sample in this study are civil servants Kilongan District Office District of North Luwuk totaling 16 people. Data were analyzed descriptively quantitatively using frequency tables and Pearson Product Moment Correlation analysis. Based on the results of the research found that non-physical work environment variables (X1) and employability (X2) have a relationship with employee performance at the Village Office Kilongan Luwuk District of North. The results showed that the correlation between non-physical work environment with the performance of employees is 0.928, while the relationship between the ability to work with the employee's performance is 0.919, which means that two independent variables have a very strong relationship with employee performance.